A Novel 12q13.2-q13.3 Microdeletion Syndrome With Combined Features of Diamond Blackfan Anemia, Pierre Robin Sequence and Klippel Feil Deformity - Roberti, Domenico; Conforti, Renata; Giugliano, Teresa; Brogna, Barbara; Tartaglione, Immacolata; Casale, Maddalena; Piluso, Giulio; Perrotta, Silverio (Frontiers in Genetics, 2018)
Diamond-Blackfan anemia (DBA) is a rare congenital erythroid aplasia with a highly heterogeneous genetic background; it usually occurs in infancy. Approximately 30-40% of patients have other associated congenital anomalies; in particular, facial anomalies, such as cleft palate, are part of about 10% of the DBA clinical presentations. Pierre Robin sequence (PRS) is a heterogeneous condition, defined by the presence of the triad of glossoptosis, micrognathia and cleft palate; it occurs in 1/8500 to 1/14,000 births. Klippel Feil (KF) syndrome is a complex of both osseous and visceral anomalies, characterized mainly by congenital development defects of the cervical spine. We describe the case of a 22-years-old woman affected by DBA, carrying a de novo deletion about 500 Kb-long at 12q13.2-q13.3 that included RPS26 and, at least, others 25 flanking genes. The patient showed craniofacial anomalies due to PRS and suffered for KF deformities (type II). Computed Tomography study of cranio-cervical junction (CCJ) drew out severe bone malfomations and congenital anomalies as atlanto-occipital assimilation (AOA), arcuate foramen and occipito-condylar hyperplasia. Foramen magnum was severely reduced. Atlanto-axial instability (AAI) was linked to atlanto-occipital assimilation, congenital vertebral fusion and occipito-condyle bone hyperplasia. Basilar invagination and platybasia were ruled out on CT and Magnetic Resonance Imaging (MRI) studies. Furthermore, the temporal Bone CT study showed anomalies of external auditory canals, absent mastoid pneumatization, chronic middle ear otitis and abnormal course of the facial nerve bones canal. The described phenotype might be related to the peculiar deletion affecting the patient, highlighting that genes involved in the in the breakdown of extracellular matrix (MMP19), in cell cycle regulation (CDK2), vesicular trafficking (RAB5B), in ribonucleoprotein complexes formation (ZC3H10) and muscles function (MYL6 and MYL6B) could be potentially related to bone-developmental disorders. Moreover, it points out that multiple associated ribosomal deficits might play a role in DBA-related phenotypes, considering the simultaneous deletion of three of them in the index case (RPS26, PA2G4 and RPL41), and it confirms the association among SLC39A5 functional disruption and severe myopia. This report highlights the need for a careful genetic evaluation and a detailed phenotype-genotype correlation in each complex malformative syndrome.